DIFFUSION OF INNOVATION IN THE RUSSIA-UKRAINE WAR: A PORTRAIT OF MODERN WARFARE EVOLUTION - Maulana, Muhammad Alfian (Indonesian Association for International Relations, 2025)
This research aims to analyze the adoption of weapon technology in the Russia-Ukraine conflict, specifically focusing on drones, Starlink, and AI-based systems, as a reflection of the evolution of modern warfare. Utilizing Everett Rogers' Diffusion of Innovations Theory, this study investigates how innovation characteristics—relative advantage, compatibility, complexity, trialability, and observability—influence the spread of technology within military systems of both sides. A qualitative approach is applied through the analysis of secondary documents, including academic reports, journal articles, and media news, with triangulation employed to ensure data validity. The main findings indicate that technology adoption dynamics are driven by urgent tactical needs and adaptive organizational structures. Both Ukraine and Russia demonstrate rapid innovation cycles through adaptation and emulation of opponent tactics. The conclusion of this research is that the successful adoption of military technology on the modern battlefield heavily relies on the perception of these innovation characteristics, as well as the capacity for adaptation within a dynamic conflict context